Finite elements based approaches for the modelling of radial crack formation upon Vickers indentation in silicon nitride ceramics. Issue 14 (November 2019) - Kadin, Yuri; Mazaheri, Mehdi; Zolotarevskiy, Vadim; Vieillard, Charlotte; Hadfield, Mark
Abstract: By having superior properties silicon nitride ceramics can be considered as the state-of-the-art material in the bearing industry. Vickers indentation of this material is typically accompanied by formation of cracks visible on surface. Two Finite Elements models are developed in the current work: the first model is based on fracture mechanics and the second on cleavage stress criterion. Plastic behavior of silicon nitride is included in the modeling, and since little is known on the plasticity of this material, the Drucker-Prager model (used for non-metallic materials) along with the classical J 2 -plasticity are explored. The results of the fracture mechanics based model correlate well with experimental results in terms of surface crack length. The numerical results in terms of the morphology of the indented zone (including cracks and plastic zone) are provided by the stress criterion based model, and these results correlate well too, with the experimental data.